The influence of Emotional Intelligence on Driving Behavior in the Transportation Sector: A literature review - Aniah, Emelia (The journal of contemporary issues in business and government, 2021)
The spate of road accidents in transportation sector around the world is so worrying that, it is imperative to look into the behaviour of drivers. One key factor that influences the behaviour of drivers is emotional intelligence. The objective of this paper is to give a systematic review of literature on the relationship between emotional intelligence and driving behaviour. The results show that, different emotional states of drivers have different effects on the behaviour of drivers. Many of the findings show that, risky driving behaviour is more associated with high emotional states. Since the emotional states of drivers affect their behaviour, it is imperative that, transport companies track the emotional states of drivers at the time they are scheduled to drive. In addition, management of all transport companies and organisational policies should consider emotional intelligence as important since emotional intelligence training programs could enhance emotional intelligence.